2017
DOI: 10.1101/229187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laws of concatenated perception: Vision goes for novelty, Decisions for perseverance

Abstract: Every instant of perception depends on a cascade of brain processes calibrated to the history of sensory and decisional events. In the present work, we show that human visual perception is constantly shaped by two contrasting forces, exerted by sensory adaptation and past decisions. In a series of experiments, we used multilevel modelling and cross-validation approaches to investigate the impact of previous stimuli and responses on current errors in adjustment tasks. Our results revealed that each perceptual r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 84 publications
6
34
1
Order By: Relevance
“…Within this line of research, it has been suggested that sequential effects may emerge in different stages of processing, ranging from early sensory to decisional stages of processing (e.g., Fornaciai & Park, 2018; Fritsche, Mostert, & de Lange, 2017; Frund, Wichmann, & Macke, 2014; St John-Saaltink et al, 2016). Some researchers argue that stimulus history might evoke contrastive effects emerging in early perceptual stages (e.g., repulsive after-effects), whereas assimilatory biases are caused by response history (Fritsche et al, 2017; Pascucci, Mancuso, Santandrea, Libera, & Plomp, 2017), whereas other studies also provide evidence for perception-based assimilatory effects (Fornaciai & Park, 2018; St John-Saaltink et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Within this line of research, it has been suggested that sequential effects may emerge in different stages of processing, ranging from early sensory to decisional stages of processing (e.g., Fornaciai & Park, 2018; Fritsche, Mostert, & de Lange, 2017; Frund, Wichmann, & Macke, 2014; St John-Saaltink et al, 2016). Some researchers argue that stimulus history might evoke contrastive effects emerging in early perceptual stages (e.g., repulsive after-effects), whereas assimilatory biases are caused by response history (Fritsche et al, 2017; Pascucci, Mancuso, Santandrea, Libera, & Plomp, 2017), whereas other studies also provide evidence for perception-based assimilatory effects (Fornaciai & Park, 2018; St John-Saaltink et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a great deal of debate surrounding the origin of sequential dependencies in perception Cicchini et al, 2017;Fritsche et al, 2017;Kiyonaga et al, 2017;Liberman et al, 2014;Pascucci et al, 2017;Suárez-Pinilla, Anil, & Roseboom, 2018), serial dependence may very likely happen at every level of visual and cognitive processing (perception, attention, decision, memory, and motor systems), and future research should investigate the interaction (and degree of independence) between all these components. Whereas our data cannot clearly disentangle between these different components, they provide further insights regarding the types of information and selectivity that serial dependence can exhibit.…”
Section: Discussionmentioning
confidence: 99%
“…To preview our results, our findings are consistent with two effects that predate Fischer and Whitney (2014): an attractive response effect (Annis & Malmberg, 2013;Jesteadt et al, 1977;Wagenmakers et al, 2004) combined with a repulsive stimulus effect (Gibson & Radner, 1937;Webster, 2015) . On this account, every response reflects both effects, to varying degrees, and this mixture has complicated the theoretical interpretation of the serial dependence effect (see also Fornaciai & Park, 2019;Fritsche et al, 2017;Manassi et al, 2018;Pascucci et al, 2019b).…”
Section: Response and A Repulsion From The Prior Stimulusmentioning
confidence: 99%
“…While it has previously been acknowledged that multiple dependencies may influence behavior simultaneously (e.g., Fornaciai & Park, 2019;Fritsche et al, 2017;Manassi et al, 2018;Pascucci et al, 2019b;Schwiedrzik et al, 2014), an important implication of this for serial dependence has not yet been highlighted: if there are two opposing dependencies, then average results plotted as a function of the difference between inducer and target will not properly reveal the magnitude of either dependency. Behavior on each trial might reflect a yin-yang summation of these complementary dependencies, with average performance SERIAL DEPENDENCE 7 across trials reflecting the relative balance between them.…”
Section: Response and A Repulsion From The Prior Stimulusmentioning
confidence: 99%
See 1 more Smart Citation